Neuroscience Tools in Branding and Packaging Marketing Research (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional De Tecnología, Ciencia Y Sociedad, 2022)
Understanding how the consumer perceives, evaluates, and chooses products, allows companies to optimize packaging design and add value that contributes to branding strategies. The evaluation of branding and packaging is a complex issue that involves cognitive processes and brain mechanisms, such as attention, memory, emotions, reward systems and decision-making. In this context, the main objective of this paper is to carry out a review of the main neuroscience tools applied to marketing research on branding and packaging by examining their theoretical basis, main metrics, advantages, limitations and uses in the study field.